Double-shelled phosphorus and nitrogen codoped carbon nanospheres as efficient polysulfide mediator for high-performance lithium-sulfur batteries - Wang, Jin (2019)
Lithium–sulfur batteries are regarded as very promising energy storage devices due to their high energy density, low cost, and environmental friendliness; however, their insulating properties and the instability of sulfur‐based electrodes impede the practical applications of Li–S batteries. Here, a versatile strategy to synthesize double‐shelled nitrogen and phosphorus codoped carbon spheres (NPDSCS) as an efficient sulfur host for Li–S batteries is reported. With strong trapping, good affinity, high adsorption for polysulfides, and the bifunctional catalyzing for sulfur redox processes, the developed NPDSCS cathodes with a high S loading of 72.4% exhibit large specific discharge capacity of 1326 mAh g−1 at 0.1C, high Coulombic efficiency, good rate capability, and excellent cycling performance with a reversible capacity of 814 mAh g−1 at 1C after 500 cycles.